Precarity aspects during the startup process. A qualitative analysis of uncertainty while founding a business at the example of Czech early-stage startups. - Bogdanov, Peter (2022)
This master thesis focuses on the topic of precarity and how early-stage start-up founders in the Czech Republic are dealing with uncertainty during the start-up process. First, the underlying problem of precarity is defined and put into the context of start-up founders in the Czech ecosystem. Next, theoretical frameworks connected to the research topic as well as the methodology connected to the data collection via semi-structured qualitative interviews is described. In the practical part of the thesis the findings of the interviews are discussed. While using a mix of deductive and inductive coding for the qualitative analysis, nine dimensions of precarity for early-stage start-up founders in the Czech Republic have been identified. Finally, after evaluating the findings, normative recommendations for founders dealing with uncertainty and precarity are obtained.